Present status of photoemission electron microscope newly installed in SPring-8 for time-resolved nanospectroscopy. (18th October 2019) - Ohkochi, Takuo; Osawa, Hitoshi; Yamaguchi, Akinobu; Fujiwara, Hidenori; Oura, Masaki
Abstract: A photoemission electron microscope (PEEM) system has been newly installed at the soft X-ray undulator beamline (BL17SU) of SPring-8 to realize time-resolved nanospectroscopy for the local transient electronic structures of advanced materials. This PEEM is a versatile machine composed of an electrostatic lens system and is intended for use in specific experiments such as time-resolved measurements. Pump–probe measurements in tandem with a femtosecond pulsed-laser system and an X-ray chopper are now readily available.